Synthesis of (E)-oxindolylidene acetate using tandem palladium-catalyzed Heck and alkoxycarbonylation reactions. Issue 1 (10th November 2015) - Lin, Wei-Jen; Shia, Kak-Shan; Song, Jen-Shin; Wu, Ming-Hsien; Li, Wen-Tai
Abstract : One-pot tandem Pd-catalyzed Heck and alkoxycarbonylation reactions for the production of new anticancer agents were established based on ( E )-oxindolylidene acetates. Abstract : Tandem reactions use consecutive reaction steps to efficiently synthesize compounds of high molecular complexity. This paper presents a tandem Pd-catalyzed Heck and alkoxycarbonylation reaction for the stereoselective synthesis of ( E )-oxindolylidene acetates. The mechanism underlying the Pd-catalyzed tandem reaction involves the syn -carbopalladation of ynamides followed by alkoxycarbonylation with CO and alcohol. This method makes it possible to obtain the desired ( E )-configuration of oxindolylidene acetates exclusively. We evaluated the scope of the reaction by applying optimal reaction conditions to the facile synthesis of a library of ( E )-oxindolylidene acetates. The resulting ( E )-oxindolylidene acetates exhibited potent anticancer activities against a variety of human cancer cell lines. The anticancer activities of some ( E )-oxindolylidene acetates were even superior to those of known CDK inhibitors indirubin-3′-oxime and roscovitine.